2014
DOI: 10.4103/0973-1482.138126
|View full text |Cite
|
Sign up to set email alerts
|

Perineural space invasion in cervical cancer (FIGO IB1-IIB) accompanied by high-risk factors for recurrence

Abstract: We were able to correlate parametrial PSI with the depth of invasion, tumor size and more advanced stage of the disease in early-stage cervical cancer with high-risk of recurrence. No association with a worse prognosis was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The occurrence of PNI was reported between 7 and 41.7% in previous studies investigating PNI in uterine cervical cancer (3)(4)(5)(6)(7). PNI is predicted to reduce the survival rate of cervical cancer patients (8)(9)(10). Thus, elucidating the mechanism of PNI and identifying markers for its early prediction are of great value for patients with early recurrence or metastasis of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of PNI was reported between 7 and 41.7% in previous studies investigating PNI in uterine cervical cancer (3)(4)(5)(6)(7). PNI is predicted to reduce the survival rate of cervical cancer patients (8)(9)(10). Thus, elucidating the mechanism of PNI and identifying markers for its early prediction are of great value for patients with early recurrence or metastasis of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been reported that the incidence of PNI in pancreatic, head and neck, prostate, gastric cancers is 98, 80, 75, and 60%, respectively (1). The incidence of PNI in cervical cancer is relatively lower than that in the aforementioned cancer types, which may be explained by extensive nerves around these tumor tissues and the strong interaction between these tumors and surrounding nerves (16). Previous studies have explored the molecular mechanisms underlying PNI associated with tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Univariate analysis suggested that parametrial PNI was one of the independent prognostic factors, and the risk of recurrence in cervical cancer patients with parametrial PNI was 2.5 times higher than that in cervical cancer patients with negative PNI. However, Skręt-Magierlo et al (16) reported that parametrial PNI was associated with clinical stage, depth of cervical stromal invasion, and tumor size, but not associated with parametrial invasion, lymph node metastasis, LVSI, and recurrence-free survival. The association between parametrial PNI and clinical stage, tumor invasion depth, tumor size, and lymph node metastasis was not conducted in the present study due to the small number of parametrial PNI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PNI has been detected in 7.0-35.1% of patients with cervical cancer who underwent radical hysterectomy and pelvic lymphadenectomy (5,(17)(18)(19)(20)(21)(22)(23) (Table I). This histological finding significantly correlates with deep cervical invasion (5,17,18,(23)(24)(25)(26), lymph-vascular space invasion (LVSI) (5,19,20,23,26), large tumor size (5,19,23,25,26), tumor extension to the uterus (19,24), positive resection margins (26), parametrial invasion (19,20,22,23,26), lymph node metastases (5,17,23,26), and more advanced stage (5, 17-19, 25, 26). Meinel et al (18) found that PNI was also PNI had a higher chance to receive adjuvant radiotherapy or concurrent chemoradiation after surgery (5,19,20,23,27).…”
Section: Carcinoma Of the Uterine Cervixmentioning
confidence: 96%